The effects of extract of Azadirachta indica (Neem) oil and Imidacloprid (IRON 30SC) on the population dynamics of Brevicoryne brassicae, Lipaphis pseudobrassicae and Plutella xylostella on white cabbage - Djomaha, E.S.; Ghogomu, R.T.; Hanna, R.; Ngatat, E.S.; Lontchi, N.F. (2016)
The effects of neem seeds oil and Imidacloprid (Iron 30SC) systemic insecticide on the populations of three cabbage pests, Brevicoryne brassicae, Lipaphis pseudobrassicae and Plutella xylostella were studied. The study was conducted between June and September 2015. Oil extracts of neem were sprayed on cabbage plants to control these pests. A standard systemic chemical insecticide (IRON 30SC) was used as comparative product. The experiment was conducted in a randomized complete block design and each treatment was replicated four times. The effects of plant extracts on the population dynamics of the pests’ species, the loss level and yield were assessed. Significantly more pests infested the control plants compared to treated plants (P ≤0.05). The mean weight of cabbage heads on the sprayed plots was not significantly heavier than that of the control unsprayed plots. The use of A. indica seeds oil and Imidacloprid systemic insecticide reduced the loss level by 6.06% and 9.92%, respectively. So, the use of this neem extracts can be ameliorated by spraying at a weekly basis and can be incorporated into an overall control programme of these pests.